The microstructure and ballistic performance of B4C/AA2024 functionally graded composites with wide range B4C volume fraction. (15th March 2019) - Chao, Z.L.; Jiang, L.T.; Chen, G.Q.; Qiao, J.; Z, Q.; Yu, Z.H.; Cao, Y.F.; Wu, G.H.
Abstract: In this research, the researchers applied the squeeze casting technology to integrally produced the B4 C/AA2024 functionally graded materials (FGMs). The volume fraction of B4 C were 70 vol%, 47 vol% and 25 vol% in the top, middle and bottom layer respectively. The ballistic tests of different samples with areal density of 80 kg/m 2 and 38 kg/m 2 were carried out using 7.62 mm armor-piercing incendiary (API). For comparison, homogeneous 70 vol% and 47 vol% B4 C/AA2024 targets were tested under the same conditions. The results demonstrate that the three layers 70-47-25 vol% B4 C/AA2024 FGMs has a better ability to maintain integrity than homogeneous 70 vol% B4 C/AA2024 target and the areal density of penetration is reduced by 14% compared to homogeneous 47% B4 C/AA2024 composites. The microstructure of targets and projectiles were investigated. Large amounts of fragmentation of B4 C particles and plastic deformation of composites are observed near the bullet hole at the top and bottom layer respectively. Crack deflection appears in the interface of the top and middle layer. By stress wave analysis, it is found that the existence of gradient structure reduces the magnitude of reflected tensile wave by 12%, which improves the ability of the target to resist fracture. The results indicate the FGMs with high ceramic content at the top layer were of good application prospects in lightweight armor. Graphical abstract: Image 1